PENGARUH OZONISASI TERHADAP DOSIS KOAGULAN PADA PERUSAHAAN AIR MINUM DI REDLAND, AUSTRALIA - Adi Mulyanto (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2000)
The experiments were conducted in the Environmental Engineering laboratory, Griffith University, Brisbane, Australia on samples provided by Redland Shire Council Waterworks. The result showed that ozonation has positive effect towards alum dosages as a coagulant. Ozone dosages were 2.86 ppm, 6.25 ppm, and 11.22 ppm, while alum dosages were 5 ppm, 10 ppm, and 15 ppm. Ca(OH)2 was utilized as pH regulator with the dosages in the range of 4 ppm – 12 ppm. Effects of ozonation on coagulant dosages were measured by color level expressed in Pt-Co units. Maximum color removal was 87% and 89% determined spectrophotometrically with the wavelength of 360 nm and 400 nm respectively.